Analiza metodyki postępowania w procesach rekrutacji pracowników naukowych - Walczak, Waldemar (Studia Edukacyjne, 2020)
The purpose of this article is to present a multifaceted analysis concerning methodology proceedin-gs in recruitment procedures for researchers. Theoretical considerations are complemented by concusions of an empirical study. The role of scientificinstitutions and values applicable in the scientificcommunity in light of popularized theories are analyzed first.Additionally, reference is made to the principles enshrined in the code of ethics of Poland’s National Research and Development Centre.Then are discussed recommended patterns of conduct which have been recorded in the European Charter for Researchers and the Code of Conduct for the Recruitment of Researchers, paying particu-lar attention to issues relating to openness and fairness of proceedings and equal treatment.The next part of the work discusses legal regulations applicable to the employment of academics at Polish universities. It looks closely into the differences that apply to employees at public and private universities, which can be considered from the point of view of legal provisions relating to the prin-ciple of equal treatment enshrined in the Constitution of the Republic of Poland.The subsequent part of study is devoted to the conclusions of an empirical study covering the compe-tition proceedings relating to the employment of academic staff at public universities. The methodo-logy of the examination procedure is thoroughly explained and interim research questions concerning the specific issues and problems closely related to the analyzed subject are presented